Neurobiological Influences on Recovery from Traumatic Brain Injury: The Role of Genetic Polymorphisms - M. Weaver, Starla; N. Portelli, Jaclyn (Current Pharmaceutical Design, 2014)
Recovery from traumatic brain injury (TBI) is variable despite similarities in the severity or mechanism of injury. The study of genetic polymorphisms offers an avenue for explaining individual differences in recovery and outcome following TBI. The current paper reviews the role that genetic polymorphisms may play in influencing recovery and quality of life following TBI. Investigating the role of polymorphisms on recovery from TBI may contribute to a better understanding of individual variations in outcome and has the potential to lead to earlier and more targeted interventions and rehabilitation based on a patient’s genetic makeup. By outlining what has been discovered about the relationship between polymorphisms and TBI we hope to both inform the medical community about the potential for polymorphisms to influence recovery following TBI and provide a roadmap to researchers about the gaps in research within this population.
Keywords: Polymorphisms